Production of MLM-type structured lipids from avocado oil catalyzed by immobilized lipase on corn cob powder: Assessment of antiproliferative potential on Hep-G2 cell line (2025)
The demand for natural and healthy products has driven research into new value-added products derived from avocado (Persea Americana var. Hass) oil. For example, the exploration of the production of structured lipids (SL), which are modified triacylglycerides with enhanced nutritional and functional properties. Enzymatic engineering of structured lipids using immobilized lipases allows for greater economy and stability under reaction conditions. In this study, medium- and long-chain structured lipids were produced from avocado oil caprylic acid byenzymatic acidolysis. Lipase from Thermomyces lanuginosus was immobilized on corn cob powder. Efficient incorporation of caprylic acid (C8:0) into avocado oil was achieved with a maximum of 31.11 % at sn-1 or sn-3 positions. However, incorporation did not occur simultaneously into triacylglycerides, and lipase reusability of up to 4 cycles. In the hepatocarcinoma cell line Hep-G2, the structured and hydrolyzed lipids inhibited cell viability, suggesting their potential for future studies related to the maintenance of liver health.